Using multimedia language lab to develop linguo-cultural competence - Popova, Oksana; Piskurska, Ganna; Skyrda, Alla; Vereshchak, Oksana (International Journal of Evaluation and Research in Education (IJERE), 2024)
The article is devoted to the problem of developing students’ linguo-cultural competence by means of a multimedia language laboratory. The multimedia language laboratory is used to create an artificial linguo-cultural environment in a regular classroom with the help of authentic audio and video materials carefully selected and methodically prepared by the teacher. The research is based on the methods of analysis and synthesis, comparison and generalization, theoretical methods related to the study of scientific literature, and experiment. In the course of the experiment, which involved 185 students, the researchers proved that the integrated use of multimedia language lab capabilities allows improving the performance and quality of students’ linguo-cultural competence, promotes the activation of educational and cognitive activities, and helps teachers in motivating their students to learn languages. The reliability of the experimental data was confirmed by the method of mathematical statistics. On the basis of the research results it is concluded that the use of the multimedia language lab makes the process of learning a foreign language more effective and dynamic and contributes to the development of students’ linguo-cultural competence.